The Importance of the Capital Market in the Financing of Public Debt (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The reasons for the emergence of public debt, its increase or decrease in size and amount are inextricably linked with the economic policy of each country, the scope and dynamics of the reforms being carried out. There are several reasons why the demand for external debt in our country has increased in recent years. The most important of them are issues of economic security, disparity between economic power and social demands, increase in the budget deficit as a result of improper use of financial resources, emergency situations, in particular, the coronavirus pandemic.